2013
DOI: 10.1083/jcb.201304003
|View full text |Cite
|
Sign up to set email alerts
|

Replication and trafficking of a plant virus are coupled at the entrances of plasmodesmata

Abstract: Plant virus movement proteins compartmentalize replication complexes at plasmodesmata for localized RNA synthesis and directional trafficking of the virus between cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(193 citation statements)
references
References 69 publications
(186 reference statements)
8
176
0
Order By: Relevance
“…Pumilio-based RNA imaging has enabled subcellular detection of the mRNAs of mitochondrial NADH dehydrogenase and -actin, as well as retroviral RNA in mammalian cultured cells (20)(21)(22)(23), and of the genomes of Tobacco mosaic virus, Potato virus X and Turnip mosaic virus in live plant tissue (24)(25)(26)(27). Of particular relevance to the topic of this volume, Pumilio-based RNA imaging has recently shown that Potato virus X is present in membrane structures at the entrances of plasmodesmata that also contain the viral replicase (27).…”
Section: Rna-binding Domain Of Pumilio Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pumilio-based RNA imaging has enabled subcellular detection of the mRNAs of mitochondrial NADH dehydrogenase and -actin, as well as retroviral RNA in mammalian cultured cells (20)(21)(22)(23), and of the genomes of Tobacco mosaic virus, Potato virus X and Turnip mosaic virus in live plant tissue (24)(25)(26)(27). Of particular relevance to the topic of this volume, Pumilio-based RNA imaging has recently shown that Potato virus X is present in membrane structures at the entrances of plasmodesmata that also contain the viral replicase (27).…”
Section: Rna-binding Domain Of Pumilio Proteinsmentioning
confidence: 99%
“…This principle is the only form of Pumilio-based RNA imaging so far applied in plants ( [24][25][26][27].…”
Section: Choice Of Reporter Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…One can speculate that after TGB1-induced structural transition this protein region might also appear to be located on the outer surface of transport-competent TGB1-bound virions similar to the localization of C-terminal PVX CP region to the outer virion surface upon protease treatment (Baratova et al, 1992), and to directly participate in interactions required for viral movement. It should be kept in mind that potexvirus cell-to-cell transport is coupled with the replication of viral RNA (Tilsner et al, 2013). Since an Ala residue in the C-terminal region of BaMV CP has been found to be involved in the CP interaction with viral replicase, and point mutations of this residue in both BaMV and Foxtail mosaic virus CPs result in the virus being unable to move from cell to cell , it is conceivable that the viral replicase binds to the CP Ctermini exposed on one end of the virion, competing therefore with the TGB1 protein.…”
Section: Role Of Virions In Cell-to-cell Transport Of Filamentous Virmentioning
confidence: 99%